The study of economics principles, concepts, & applications - Mings, Turley (ConnecText, 2000)
This text offers ana analysis of the basic principles and concepts of economics and goes on to illustrate these with applications from the economic scene in the late 1990s. The books covers: fundamental concepts; microeconomics; macroeconomics; and the global economy.